PENGEMBANGAN MEDIA PRAKTIKUM BERBASIS EXCEL MATERI PEMERIKSAAN KARBOHIDRAT (GLUKOSA, SUKROSA DAN FRUKTOSA) UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS - Ibnu Khaldun; Andi Ulfa Tenri Pada; Zulfadli Zulfadli; Hafnati Rahmatan; Muhammad Nazar; Nunung Sri Mulyani; Susi Andayani (Postgraduate, University of Mataram, 2022)
Science process skills have the potential to build students' basic competencies. There are many factors that influence this skill, one of which is the proper use of media. The development of excel-based practicum media is one of the solutions to solve this problem. The aim of the research is to improve students' science process skills in doing practicum. This study has a Research and Development (R&D) design with a population of 132 people with a sample of 66 people using a purposive sampling technique. includes media feasibility 0.72 or high, visual communication 0.35 or moderate, and material 0.45 or moderate. The reliability test obtained 0.000, which means that the similarity between the ratings given by the two validators is very low. In conclusion, the developed media meets the requirements to be used as a research instrument.